Uniform Crime Reporting Program Data (United States): County-Level Detailed Arrest and Offense Data, 1995 ([Verlag nicht ermittelbar], 1997)
This data collection contains county-level counts of arrests and offenses for Part I offenses (murder, rape, robbery, aggravated assault, burglary, larceny, auto theft, and arson) and Part II offenses (forgery, fraud, embezzlement, vandalism, weapons violations, sex offenses, drug and alcohol abuse violations, gambling, vagrancy, curfew violations, and runaways).